2022
DOI: 10.7759/cureus.29372
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging the Role of Community Health Workers in Providing Essential Healthcare Services in Rural India-A Review

Abstract: In underserved communities, the community health worker (CHW) concept has been employed to improve health and lessen unfavourable health consequences. In India's rural healthcare delivery system, auxiliary nurse midwives (ANMs), accredited social health activists (ASHA workers), and Anganwadi workers (AWWs) are the primary field-level frontline officials who come into direct contact with the population. They bear a large portion of the burden of carrying out health services. This review investigated the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, many studies within health systems also argue that the absence of incentives is largely viewed as inadequate compensation for the quantum of effort invested (Scott et al, 2018;Ormel et al, 2019;Olaniran et al, 2022). This was also seen across several studies closer to the context of the present study (Scott et al, 2019;John et al, 2020;Scott and Shanker, 2010;Kalne et al, 2022). Consequently, the demand for fair remuneration is increasingly growing across LMICs including India, especially because most health workers come from poorer socio-economic backgrounds with limited alternative livelihood options (Barria et al, 2018;John et al, 2020).…”
Section: Identification Of Agents: Diagnosing Self-interestmentioning
confidence: 54%
See 1 more Smart Citation
“…However, many studies within health systems also argue that the absence of incentives is largely viewed as inadequate compensation for the quantum of effort invested (Scott et al, 2018;Ormel et al, 2019;Olaniran et al, 2022). This was also seen across several studies closer to the context of the present study (Scott et al, 2019;John et al, 2020;Scott and Shanker, 2010;Kalne et al, 2022). Consequently, the demand for fair remuneration is increasingly growing across LMICs including India, especially because most health workers come from poorer socio-economic backgrounds with limited alternative livelihood options (Barria et al, 2018;John et al, 2020).…”
Section: Identification Of Agents: Diagnosing Self-interestmentioning
confidence: 54%
“…This was also seen across several studies closer to the context of the present study (Scott et al ., 2019; John et al. , 2020; Scott and Shanker, 2010; Kalne et al ., 2022). Consequently, the demand for fair remuneration is increasingly growing across LMICs including India, especially because most health workers come from poorer socio-economic backgrounds with limited alternative livelihood options (Barria et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study has demonstrated support for the hypothesis that there is a direct relationship between CHWs’ affective organizational commitment, innovative behaviour, and burnout prevention. This challenges earlier reports on the hospital industry [10] [11] but adds valuable information to the existing literature on public health to foster innovation and the mental health of employees.…”
Section: Resultsmentioning
confidence: 76%
“…Studies have identified sources of motivation for CHWs at the individual, family, community, and organisational levels, but lack attention to psychological factors that influence CHWs' motivation and job satisfaction [12]. This information is relevant to CHW burnout, and employee retention issues in the health sector [11]. Are our CHWs ready to innovate to address dynamic challenges at work?…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation